Respuesta :
Answer:
C. [tex]h(x)=x-3[/tex]
Step-by-step explanation:
We have been given a function [tex]f(x)=x+3[/tex]. We are asked to find the inverse of the given function.
First of all, we will replace [tex]f(x)[/tex] by y as:
[tex]y=x+3[/tex]
Now, we will interchange x and y variables as:
[tex]x=y+3[/tex]
Solve for y:
[tex]x-3=y+3-3[/tex]
[tex]x-3=y[/tex]
Switch sides:
[tex]y=x-3[/tex]
Therefore, the inverse function for the given function would be [tex]h(x)=x-3[/tex].
Answer:
C
Step-by-step explanation:
I did it on EDGE 2020 Mid Term Test Review